Power-balancing compensation mechanism and method for controllable load reduction - Sun, Yalu; Ding, Kun; Du, Wenlu; Yang, Changhai; Li, Yalong (Frontiers in Energy Research, 2023)
In the high proportion of new energy connected system, it is easy to appear the absolute power vacancy caused by the power supply that is less than the demand, and the prediction error vacancy caused by the small predicted value of new energy in the day during the peak load period. In order to ensure the power supply balance, it is urgent to mobilize controllable loads to reduce power consumption through the compensation mechanism. This paper first constructs a double compensation mechanism for the reduced load by the non-reduced load and new energy enterprise. Secondly, based on the principle of Sequential Auction and proportional distribution according to the reduction loss, a compensation method for the reduced load by the non-reduced one is proposed. Considering both the reduction of electricity consumption and the carbon emission rate indicator, a compensation method for the reduced load by new energy enterprise is proposed; then, the compensation method and process of the controllable load reduction are formed. Finally, the feasibility of the method described in this paper is verified by an example.